Peran Pemerintah dalam Membangun Narasi Kebangsaan melalui Komunikasi Krisis Berbasis Pancasila - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Namira Lingga Sastro Nugroho; Devi Nurul Affla; Amelia Diah Rosita; Atikah Firdaus (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This study aims to examine the role of the government in building a national narrative through Pancasila-based crisis communication. The focus of the study includes crisis communication and national stability, challenges of the digital era, transparency, public participation, media collaboration, policy strengthening, and measuring communication effectiveness. The method used is qualitative with content analysis of government policies, public communication materials, and mass media coverage. The study also examines the public response to government messages in the national crisis. The results show that the government uses mass media, social media, and direct communication to convey national messages based on Pancasila. Collaboration with educational institutions, community leaders, and community organizations strengthens the reach of communication. The government's planned and responsive communication strategy is effective in reducing social tensions, strengthening the spirit of nationalism, and maintaining the relevance of Pancasila amid social dynamics. These findings contribute to the development of crisis communication theory and practice in the context of nationality.